Q: How do you factor x3 2x2 5x 4?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

x3 + 2x2 - 19x - 20 = x3 + x2 + x2 + x - 20x - 20 = x2(x + 1) - x(x + 1) - 20(x + 1) = (x + 1)(x2 + x - 20) = (x + 1)(x - 4)(x + 5)

25x2 + 40x + 16 = 25x2 + 20x + 20x + 16 = 5x(5x + 4) + 4(5x + 4) = (5x + 4)(5x + 4) or (5x + 4)2

Discriminant = 52 - 4 x 2 x (-8) = 89

x3 + x2 + 4x + 4 = (x2 + 4)(x + 1)

Related questions

2x2 - 5x + 12 does not factor. 2x2 - 5x - 12 factors into (2x + 3)(x - 4) 2x2 + 5x - 12 factors into (2x - 3)(x + 4)

2X2+5x-12 4+5x-12 -8+5x 5x-8

Show the terms as additive here..., 8X2 + 10X3 factor out 2X2 2X2(4 + 5X) ---------------- 2X2 ==== greatest common factor

x3 - 2x2 - 4x + 8 = (x2 - 4)(x - 2) = (x + 2)(x - 2)(x - 2)

x3 - 4x2 + 5x - 20 = x2*(x - 4) + 5*(x - 4) = (x2 + 5)*(x - 4)

(x + 2)(x^2+4)

Differentiate the function with respect to x: d/dx (x3 - 2x2 - 5x + 6) = 3x2 - 4x - 5 Set this derivative = 0 and solve. 3x2 - 4x - 5 = 0 implies that x = -0.7863 or 2.1196 (to 4 dp)

If that's 2x2, the answer is (x + 2)(x2 + 4)

x3 + 3x2 - 6x - 8 = (x - 2)(x2 + 5x + 4) = (x - 2)(x + 1)(x + 4)

You would first factor out anything that is common between the 3 parts. 2x2 is the greatest common factor. To pull out the 2x2, you divide each term by 2x2 like so:12x4/2x2=6x210x3/2x2=5x-12x2/2x2=-6We now know that 12x4+10x3-12x2= 2x2(6x2+5x-6)The next step involves using the "slip and slide" method for the trinomial inside the parentheses:6x2+5x-6x2+5x-36(x+9)(x-4)(x+9/6)(x-4/6)(x+3/2)(x-2/3)(2x+3)(3x-2)Remembering that the result for the slip and slide method only accounts for 6x2+5x-6 we must multiply (2x+3)(3x-2) by 2x2.Your final answer is 2x2(2x+3)(3x-2).

x3 + 2x2 - 19x - 20 = x3 + x2 + x2 + x - 20x - 20 = x2(x + 1) - x(x + 1) - 20(x + 1) = (x + 1)(x2 + x - 20) = (x + 1)(x - 4)(x + 5)

(x3 + 3x2 - 2x + 7)/(x + 1) = x2 + 2x - 4 + 11/(x + 1)(multiply x + 1 by x2, and subtract the product from the dividend)1. x2(x + 1) = x3 + x22. (x3 + 3x2 - 2x + 7) - (x3 + x2) = x3 + 3x2 - 2x + 7 - x3 - x2 = 2x2 - 2x + 7(multiply x + 1 by 2x, and subtract the product from 2x2 - 2x + 7)1. 2x(x + 1) = 2x2 + 2x2. (2x2 - 2x + 7) - (2x2 + 2x) = 2x2 - 2x + 7 - 2x2 - 2x = -4x + 7(multiply x + 1 by -4, and subtract the product from -4x + 7)1. -4(x + 1) = -4x - 42. -4x + 7 - (-4x - 4) = -4x + 7 + 4x + 4 = 11(remainder)